Interfacial behavior of tetrapyridylporphyrin monolayer arrays - Ruggles, Jeremy L (Langmuir : the ACS journal of surfaces and colloids, 2006)
The behavior of monolayer films of free base 5,10,15,20-tetrapyridylporphinato (TPyP) and 5,10,15,20-tetrapyridylporphinato zinc(II) (ZnTPyP) on pure water, 0.1 M CdCl2, and 0.1 M CuCl2 subphases was investigated by surface pressure-area isotherms, specular X-ray reflectometry, and polarized total reflection X-ray absorption spectroscopy (PTRXAS). Surface pressure-area isotherms showed significant differences in the area per molecule on pure water compared to that on salt subphases, with a marked increase in the area observed on the salt solutions. This behavior was noted for both forms of the porphyrin and both salts investigated. Modeling of specular X-ray reflectometry data indicated that thinner and more electron dense layers on salt subphases best fit the observed profiles. These data suggest that the porphyrin macrocycle is oriented parallel to the interface on salt subphases and takes on a tilted conformation on pure water. In the case of ZnTPyP, PTRXAS was used to determine the orientation of the porphyrin moiety relative to the surface and to probe the coordination of the central Zn ion. In agreement with the pressure-area isotherms and reflectometry, the PTRXAS data indicate a change in orientation on the salt subphases